Factors affecting soft cost in BIM-based construction projects - M. Farouk, Abdelrahman; Ahmad Tarmizi, Haron; Papadonikolaki, Eleni; Rahimi, A. Rahman (Engineering Project and Production Management, 2025)
Building Information Modeling (BIM) is transforming the construction industry by improving project efficiency, accuracy, and teamwork. However, not determining soft costs in BIM-based construction projects accurately can lead to financial uncertainties and management issues, making it difficult to assess the return on investment (ROI) of BIM. Identifying the factors that influence BIM soft costs is crucial for determining the ROI of BIM. To address this issue, this study aims to investigate the factors affecting soft costs in BIM-based construction projects, using Malaysia as a case study. Data collection involved conducting semi-structured interviews with BIM professionals, followed by thematic analysis to analyze the collected data. The findings revealed that the factors influencing soft costs can be categorized into two main themes: organizational factors and project factors. Within organizational factors, subthemes included development charges, certification fees, commissioning fees, and ongoing maintenance costs. On the contrary, project factors encompassed contingency fees, levy fees, and documentation fees. Understanding these factors is crucial for determining the ROI of BIM, which can drive more widespread BIM implementation in developing countries. The study reveals that accurately identifying the factors influencing soft costs in BIM-based construction projects is essential for effective cost management. As a result, the findings emphasize the importance of addressing these factors to improve financial planning and project execution in the construction industry. The originality of this study lies in its focus on soft costs within BIM-based construction projects, an area underexplored in existing literature. This nuanced understanding helps organizations and policymakers manage costs more effectively, contributing to more efficient construction practices and supporting the UN Sustainable Development Goals 9: Industry, Innovation, and Infrastructure and 11: Sustainable Cities and Communities by promoting sustainable building practices and resilient infrastructure development.